THE ROLE OF INTRINSIC AND EXTRINSIC MOTIVATION IN PERSONAL SUCCESS - Babayeva, Elnara (Revista Gênero e Interdisciplinaridade, 2025)
This study aims to examine the role of intrinsic and extrinsic motivation in achieving personal success, focusing on how these motivational factors influence students’ accomplishments in Azerbaijani universities. Using standardized instruments - Motivation Assessment Scale (Michael J. Delaney and Mark Durand, Ph.D. 1986) and an adapted The Achievement Motivation Scale (Cassidy & Lynn, 1989) - the study explores relationships between motivational orientations and perceived personal achievement.Sample: 410 undergraduate and graduate students from various Azerbaijani higher education institutions participated. Methods: Data were analyzed using IBM SPSS Statistics, Version 31.0. Descriptive statistics, reliability tests (Cronbach’s alpha), Pearson’s correlation coefficients, and multiple linear regression analyses were conducted to examine relationships between variables.Results: Both intrinsic and extrinsic motivation significantly predicted perceived personal success (β = 0.312 and β = 0.567 respectively, p < .001). Extrinsic motivation showed a stronger association with short-term achievement indicators, while intrinsic motivation related to sustained engagement and self-reported fulfillment.Significance: Findings emphasize the need for balanced educational practices that nurture both intrinsic interests and appropriate external supports to foster students’ holistic success.